Emergency Physicians Accurately Interpret Video Capsule Endoscopy Findings in Suspected Upper Gastrointestinal Hemorrhage: A Video Survey. (16th July 2013) - Meltzer, Andrew C.; Pinchbeck, Carrie; Burnett, Sarah; Buhumaid, Rasha; Shah, Payal; Ding, Ru; Fleischer, David E.; Gralnek, Ian M.; Lewis, Lawrence
Abstract Background Acute upper gastrointestinal (GI) hemorrhage is a common emergency department (ED) presentation whose severity ranges from benign to life‐threatening and the best tool to risk stratify the disease is an upper endoscopy, either by scope or by capsule, a procedure performed almost exclusively by gastroenterologists. Unfortunately, on‐call gastroenterology specialists are often unavailable, and emergency physicians (EPs) currently lack an alternative method to endoscopically visualize a suspected acute upper GI hemorrhage. Recent reports have shown that video capsule endoscopy is well tolerated by ED patients and has similar sensitivity and specificity to endoscopy for upper GI hemorrhage. Objectives The study objective was to determine if EPs can detect upper GI bleeding on capsule endoscopy after a brief training session. Methods A survey study was designed to demonstrate video examples of capsule endoscopy to EPs and determine if they could detect upper GI bleeding after a brief training session. All videos were generated from a prior ED‐based study on patients with suspected acute upper GI hemorrhage. The training session consisted of less than 10 minutes of background information and capsule endoscopy video examples. EPs were recruited at the American College of Emergency Physicians Scientific Assembly in Denver, Colorado, from October 8, 2012, to October 10, 2012. Inclusion criteria included being an ED resident or attending physician and the exclusion criteria included any formal endoscopy training. The authors analyzed the agreement between the EPs and expert adjudicated capsule endoscopy readings for each capsule endoscopy video. For the outcome categories of blood (fresh or coffee grounds type) or no blood detected, the sensitivity and specificity were calculated. Results A total of 126 EPs were enrolled. Compared to expert gastroenterology‐adjudicated interpretation, the sensitivity to detect blood was 0.94 (95% confidence interval [CI] = 0.91 to 0.96) and specificity was 0.87 (95% CI = 0.80 to 0.92). Conclusions After brief training, EPs can accurately interpret video capsule endoscopy findings of presence of gross blood or no blood with high sensitivity and specificity.